PENJELASAN KARAKTER KERJA SAMA DALAM FISIKA - Aizinsh, Marcis; Oktavia, Sri Wina; Firmansyah, Riko; Ruttinawati, Ruttinawati (EduFisika: Jurnal Pendidikan Fisika, 2023)
This study aims to identify how the character of student cooperation through indicators of good listeners and respect for others. This type of research is a mixed-method type of explanatory approach. While the research instrument uses questionnaires and interviews, data analysis uses descriptive tests and descriptions. The sampling technique used purposive sampling. The results of the study showed students on the mutually encouraging aspect of the cooperation character indicator Junior High School 16 Muaro Jambi with a percentage of 70% in the good category, Junior High School 18 Kerinci with a percentage of 66% in the good category, Valmiera Secondary School with a percentage of 45% in the very good category, and Valmiera Viesturs secondary school percentage is 54% very good category. Furthermore, students in the aspect of helping each other from the indicator of the character of cooperation Junior High School 16 Muaro Jambi with a percentage of 46% in the very good category, Junior High School 18 Kerinci with a percentage of 75.5% in the good category, Valmiera Secondary School with a percentage of 79.1% in the good category, and Valmiera Viesturs secondary school percentage of 54% very good category.